Volatiles and Intraplate Magmatism: a Variable Role for Carbonated and Altered Oceanic Lithosphere in Ocean Island Basalt Formation. (12th April 2023) - Kirstein, Linda A; Walowski, Kristina J; Jones, Rosemary E; Burgess, Ray; Fitton, J Godfrey; De Hoog, Jan C M; Savov, Ivan P; Kalnins, Lara M
Abstract: Recycling of material at subduction zones has fundamental implications for melt composition and mantle rheology. Ocean island basalts (OIBs) sample parts of the mantle from variable depths that have been diversely affected by subduction zone processes and materials, including the subducted slab, metasomatising melts and fluids. Resultant geochemical differences are preserved at a variety of scales from melt inclusions to whole rocks, from individual islands to chains of islands. Here we examine a global dataset of ocean island basalt compositions with a view to understanding the connection between silica-saturation, olivine compositions, and halogens in glass and olivine-hosted melt inclusions to reveal information regarding the mantle sources of intraplate magmatism. We find that minor elements incorporated into olivine, although informative, cannot unambiguously discriminate between different source contributions, but indicate that none of the OIB analysed here are derived solely from dry peridotite melting. Nor can differences in lithospheric thickness explain trace element variability in olivine between different ocean islands. We present new halogen (F, Cl, Br/Cl, I/Cl) data along with incompatible trace element data for the global array and encourage measurement of fluorine along with heavier halogens to obtain better insight into halogen cycling. We suggest that Ti-rich silica-undersaturated melts require a contribution from carbonated lithosphere, either peridotite or eclogite and are an important component sampled by ocean island basalts, together with altered oceanic crust. These results provide new insights into our understanding of mantle-scale geochemical cycles, and also lead to the potential for the mantle transition zone as an underestimated source for observed volatile and trace-element enrichment in ocean island basalts.